The Efforts of Implementing the 21st Century Learning in English Education - Kurniati Kurniati; Vina Ervina; Nabila Ainatasya; Ahmad Jailani (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2024)
This research aims to reveals the efforts of implementing 21st century learning and the challenges faced by respondents in applying 21st century learning in English Education Study program at STAIN Bengkalis. This study was a survey research. The findings indicated that several efforts to implement 21st century learning conducted by lecturers in the English Education Study Program at STAIN Bengkalis included: 1) In general, the lecturers have implemented 21st century learning models such as Collaborative Learning, Project Based Learning, and Problem Based Learning; 2) Lecturers employed student-centered learning methods; and 3) Digital literacy was utilized by lecturers in the teaching processes. Meanwhile, some challenges faced are: 1) Inadequate facilities and infrastructure; 2) Many students still lack proficiency in digital literacy; 3) Students face difficulties in mastering the 4C skills (Critical Thinking and Problem Solving, Communication Skills, Creativity and Innovation Skills, and Collaboration Skills); and 4) The concept and principles of 21st century learning are not fully understood by lecturers and students. In order to support better implementation of 21st century learning, institution should provide enough facilities and a workshop about how to implement 21st learning.